Modeling of Cryogenic Liquefied Natural Gas Ambient Air Vaporizers - Sun, Biao; Wadnerkar, D.; Utikar, Ranjeet; Tade, Moses; Kavanagh, N.; Faka, S.; Evans, G.; Pareek, Vishnu (American Chemical Society, 2018)
The ambient air vaporizer (AAV) technology is a promising option for vaporization of cryogenic fluids including liquefied natural gas (LNG). In this study, the heat transfer between ambient air and cryogenic LNG under supercritical conditions has been studied by using computational fluid dynamics (CFD). The process of regasification was first analyzed from the thermodynamics standpoint. In the absence of actual data for LNG, the empirical correlations and experimental data for supercritical flows of water and carbon dioxide were used to validate the CFD model. The model was then used to investigate the supercritical flow of LNG inside AAV. Operating conditions such as air flow velocity and operating pressure were studied. Furthermore, optimization of fin configurations including the number of fins, fin length, and fin thickness was also investigated. The methodology and results discussed in this study are of critical importance for designing AAV.